2014
DOI: 10.3390/molecules19032896
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Complex Antimicrobial Interactions of Essential Oils — The Case of Thymus vulgaris (Thyme)

Abstract: Abstract:Thymus vulgaris has gained tremendous popularity as an ornamental, culinary herb and its use in phytotherapy is well established and supported in the literature. The objective of this study was to explore possible interactions between selected molecules within Thymus vulgaris essential oil (TvEO) to gain a better understanding of how this complex essential oil exerts its antimicrobial activity. Evaluation of the antimicrobial efficacy and interactions were assessed on the essential oil and volatile co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 22 publications
5
55
0
Order By: Relevance
“…tuber-303 culosis, malaria etc. The main aim of combination therapy is to achieve 304 synergy, reducing drug dosage and minimizing or delaying the onset 305 of drug resistance (Van Vuuren and Viljoen 2011; Ahmad et al 2014). 306 The differences in chemical compositions of the CEO, irrespec-307 tive of qualitative and/or quantitative differences with the previously 308 published papers, restrict the validity of these interesting biologi-309 cal results to the CEO's with similar chemical compositions.…”
mentioning
confidence: 96%
“…tuber-303 culosis, malaria etc. The main aim of combination therapy is to achieve 304 synergy, reducing drug dosage and minimizing or delaying the onset 305 of drug resistance (Van Vuuren and Viljoen 2011; Ahmad et al 2014). 306 The differences in chemical compositions of the CEO, irrespec-307 tive of qualitative and/or quantitative differences with the previously 308 published papers, restrict the validity of these interesting biologi-309 cal results to the CEO's with similar chemical compositions.…”
mentioning
confidence: 96%
“…These differences could be explained by the variety of mechanisms of action attributable to the essential oil compounds and the possible synergistic effect between them (Ahmad et al . ; Said et al . ).…”
Section: Resultsmentioning
confidence: 95%
“…7.0 software (GraphPad Software, Inc. California, CA) to present the FIC index of the combinations (Ahmad et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is believed that the hydroxyl group on these compounds interact on the cytoplasmic membrane and changes its permeability by affecting lipid ordering and stability of its bilayer. Therefore proton passive flux across the membrane increased, which disrupted the cytoplasmic membrane and leading to leakage of cellular contents [35][36][37][38]. Antifungal activity of the essential oil of T. vulgaris L. and Thymol on experimentally induced dermatomycoses was carried out by Sokovi et al [29] and found excellent results.…”
Section: T Vulgaris An Important Spice Is Widely Used In Various Ailmentioning
confidence: 96%